Transitioning to net zero: Full potential of sustainable finance taxonomies not yet exhausted - Catherine Marchewitz; Franziska Schütze; Fernanda Ballesteros (DIW Weekly Report, 2024)
Sustainable finance taxonomies such as the European Union (EU) taxonomy can support the transition to a climate-neutral economy. As a classification system, these taxonomies serve to offer transparency and guidance as to how capital flows can be shifted to sustainable and environmentally-friendly activities. In this Weekly Report, we analyze 26 sustainable taxonomies from countries and regions around the world using five criteria. Our study shows that although many taxonomies follow a holistic sustainability approach, mandatory criteria have often yet to be developed. The share of a country or region's emissions that is covered by the taxonomy varies considerably, as the taxonomies follow different approaches for determining the activities that are aligned with them. Taxonomies often only apply to a limited group of market participants and are rarely linked to mandatory reporting obligations. The results emphasize that better coordination between the existing taxonomies worldwide is needed and that the criteria and thresholds for selecting activities in alignment with taxonomies should be in accordance with the Paris Agreement. This way, taxonomies can develop their full potential in guiding the transition.
Keywords: G18; P00; Q01; Q58; 330; ustainable Finance Taxonomy; Green Finance; Transition Finance; EU Taxonomy; climate policy; transition plans